Cash Flow-Predictability: Still Going Strong - Maik Schmeling; Jesper Rangvid; Andreas Schrimpf (Verein für Socialpolitik, 2010)
The common perception in the literature is that current dividend yields are uninformative about future dividends, but contain some information about future stock returns. In this paper, we show that this finding reverses when looking at a broad panel of countries outside the U.S.. In particular, we demonstrate that aggregate dividend growth rates are highly predictable by the dividend yield and that dividend predictability is clearly stronger than return predictability in medium-sized and smaller countries that account for the majority of countries in the world. We show that this is true both in the time-series dimension (time variation in dividend yields strongly predicts future dividend growth rates) and in the cross-country dimension (sorting countries into portfolios depending on their lagged dividend yield produces a spread in dividend growth rates of more than 20% p.a.). In an economic assessment of this finding, we show that cash flow predictability is stronger in smaller and medium-sized countries because these countries also have more volatile cash flow growth and higher idiosyncratic return volatility.
Keywords: G12; G15; F31; 330; dividend yield; predictability; international stock markets; value; growth; idiosyncratic volatility